An overview of industrial Knowledge Management System and a review of Access Control Methods / Putri Norlyana Mustafa Kamal, Azmi Osman and Norlida Buniyamin - Mustafa Kamal, Putri Norlyana; Osman, Azmi; Buniyamin, Norlida (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
Companies are now realizing the importance of retaining and sharing organizational knowledge, this paper presents the need for a secure and reliable Knowledge Management System (KMS) for manufacturing organisations. Although previous researches have mentioned that KMS security is important, it has not been a focus in previous researches in this area. Previous research in the areas of KMS & Access Control Method (ACM) is summarized in this paper. A literature review was conducted to study the relationship between KMS and ACM, and also to find a research gap in ACM. This paper introduces an ongoing research conducted in a manufacturing company in Malaysia. The aim of the research is to develop and implement a KMS with ACM for security by applying an improved version of Role-Based Access Control (RBAC). The improved RBAC is expected to overcome current RBAC’s weakness which is rigidity and requirement for complex management.